Finding a replacement for the soul : mind and meaning in literature and philosophy - Bourbon, Brett, 1963- (Harvard University Press, 2004)
Approaching the study of literature as a unique form of the philosophy of language and mind - as a study of how we produce nonsense and imagine it as sense - this is a book about our human ways of making and losing meaning.